2014
DOI: 10.2961/jlmn.2014.03.0019
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Modulated Laser Beam Micro Welding of CuSn6 and Nickel-plated DC04 Steel for Battery Applications

Abstract: The emerging fabrication techniques for transparent materials such as glass and crystal that use focused ultra-short laser pulses will be reviewed from the viewpoint of functionalities of the products to be integrated into a future photonic system. The devices include waveguide and waveguide couplers, mirrors and lenses, filters and holograms. The future photonic system may consist of many functional subsystems which are connected through transparent gates or windows. Welding technique may play an important ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…13(a)). In order to increase the contact area and to get a stable welding depth, superimposed beam oscillation can be applied [29,30]. In Fig.…”
Section: Laser Beam Weldingmentioning
confidence: 99%
“…13(a)). In order to increase the contact area and to get a stable welding depth, superimposed beam oscillation can be applied [29,30]. In Fig.…”
Section: Laser Beam Weldingmentioning
confidence: 99%
“…This makes it possible to widen the narrow weld seams and to improve the mechanical, thermal, and electrical properties of the welded connection. [13,22] As a result, local modulation has become more important, especially for joining copper and aluminum. Oscillatory motion is generated by the superposition of two periodic, orthogonal motions.…”
Section: Theoretical Principlesmentioning
confidence: 99%
“…Possible oscillating movements are linear (one-dimensional movement transverse to the feed direction), circular, elliptical, and octagonal. The use of circular oscillation has gained acceptance in laser beam micro welding because experiments have shown that molten pool ejections are reduced compared to other forms of oscillation and conventional welding [22][23][24].…”
Section: Theoretical Principlesmentioning
confidence: 99%
“…Several welding techniques have been identified by researchers for automotive battery pack manufacturing e.g., laser beam welding (LBW), resistance spot welding and ultrasonic welding process [5,56]. Of these LBW is preferred for welding individual battery cells [6][7][8][9][10][11][12] due to its advantages of high-power density, small heat-affected zone, high welding speed, reproducibility, flexibility, easy automation and non-contact joining etc. Brand et al [6], investigated different welding techniques (e.g., resistance spot welding, ultrasonic welding and laser beam welding) for battery cell to tab welding, and studied the electrical contact resistance of the welds produced.…”
Section: Introductionmentioning
confidence: 99%